The Eschatological Dimension of the Seventh-day Sabbath in the Synoptic Gospels - Zoltán Szallós-Farkas (TheoRhēma, 2019)
What is argued in this paper is that the Synoptic Gospels present a theology of the seventh-day Sabbath in which its crucial importance is seen to have resided in its uninterrupted spatio-temporal and historical validity and availability. Thus, the Sabbath features as the temporal context for Christ’s speciﬁcally messianic ministry, sayings, and religious practice. As such, it has not been spiritualized in the Gospels of Matthew, Mark, and Luke. Rather, the Synoptic writers are intent on convincing the reader with regard to a quite novel fact, namely, that Jesus’ Sabbath theology and practice shed light on how God’s Creation world order is going to be literally reestablished through his messianic ministry. Stated diﬀerently, in Matthew’s, Mark’s, and Luke’s Gospel, the seventh-day Sabbath constitutes a typological pointer whereby the ﬁnal eschatological restoration of God’s kingdom and rule are to be understood in the light of the fact that such restoration is already taking place, spatially and temporally, in our present fallen world, while also climaxing towards the spatio-temporally perceptible future event of the reconstitution of the new heaven and the new earth, at the second coming of Christ.